Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0178848
|View full text |Cite
|
Sign up to set email alerts
|

Desire for a child and eating disorders in women seeking infertility treatment

Abstract: ObjectivesThe purpose of this study was to evaluate the prevalence of EDs in women seeking treatment for infertility, and to better characterize their clinical profile.Study designSixty participants completed self-report measures that assessed EDs, desire for a child, body preoccupations, quality of life, anxiety and depression.ResultsTen patients (17%) met criteria for a past or current ED. We showed a significant association between greater body dissatisfaction and a more ambivalent desire for a child. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
0
17
0
3
Order By: Relevance
“…These favourable results in terms of diet after confinement could be related to the lower global levels of anxiety and depression (HADS-Total) reported by the participants when the reproduction service was reopened compared to during confinement. In fact, some authors have observed that infertile women with higher anxiety levels exhibited poorer eating behaviours ( 39 ). However, despite this observed improvement in diet, 68.2% of the participants showed adherence levels lower than recommended.…”
Section: Discussionmentioning
confidence: 99%
“…These favourable results in terms of diet after confinement could be related to the lower global levels of anxiety and depression (HADS-Total) reported by the participants when the reproduction service was reopened compared to during confinement. In fact, some authors have observed that infertile women with higher anxiety levels exhibited poorer eating behaviours ( 39 ). However, despite this observed improvement in diet, 68.2% of the participants showed adherence levels lower than recommended.…”
Section: Discussionmentioning
confidence: 99%
“…: – IF with IHH: 95.2% LTP ED (N = 20) of which: 85% AN (N = 19), 5% BN (N = 1) – Control group: 23.8% LTP ED restrictive type AN (N = 5) Phen . : – BMI IF IHH lower compared to other types of infertility* – Normal BMI in control group Bruneau et al 2017 [ 8 ] Obj. : assessing prev.…”
Section: Resultsmentioning
confidence: 99%
“…Dies kann zu einem unzureichenden Kontrazeptivagebrauch und dem Risiko ungeplanter Schwangerschaften insbesondere bei Frauen mit Anorexie und Bulimie führen [11]. Auf der anderen Seite unterziehen sich diese Frauen häufiger einer Fruchtbarkeitsbehandlung [12] Bei einem Großteil der schwangeren Frauen kommt es intra partum zu einer vorübergehenden Linderung der Essstörungssymptomatik, da die Motivation, dem ungeborenen Kind eine optimale Gesundheit zu gewährleisten, überwiegt [18]. In seltenen Fällen kann die Schwangerschaft einen Risikofaktor für den erneuten Ausbruch oder die Verschlechterung von Essstörungen darstellen [19].…”
Section: Essstörungenunclassified